Imputting missing DNA microarray data using nearest neighbour (NN) in least square data imputation algorithm for survival analysis - Cham, Wei Lun, 1986-; Afnizanfaizal Abdullah, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (2010)
Project Paper (Sarjana Muda Sains (Bioinformatik)) - Universiti Teknologi Malaysia, 2010